TNF-Receptor-Associated Factor 3 in Litopenaeus vannamei Restricts White Spot Syndrome Virus Infection Through the IRF-Vago Antiviral Pathway - Li, Haoyang; Fu, Qihui; Wang, Sheng; Chen, Rongjian; Jiang, Xiewu; Zhu, Peng; He, Jianguo; Li, Chaozheng (Frontiers in Immunology, 2020)
Tumor necrosis factor receptor (TNFR)-associated factors (TRAFs) are vital signaling adaptor proteins for the innate immune response and are involved in many important pathways, such as the NF-кB- and IRF-activated signaling pathways. In this study, the TRAF3 ortholog from the shrimp Litopenaeus vannamei (LvTRAF3) was cloned and characterized. LvTRAF3 has a transcript of 3,865 bp, with an open reading frame (ORF) of 1,002 bp and encodes a polypeptide of 333 amino acids, including a conserved TRAF-C domain. The expression of LvTRAF3 in the intestine and hemocyte was up-regulated in response to poly (I:C) challenge and white spot syndrome virus (WSSV) infection. RNAi knockdown of LvTRAF3 in vivo significantly increased WSSV gene transcription, viral loads, and mortality in WSSV-infected shrimp. Next, we found that LvTRAF3 was not able to induce the activation of the NF-кB pathway, which was crucial for synthesis of antimicrobial peptides (AMPs), which mediate antiviral immunity. Specifically, in dual-luciferase reporter assays, LvTRAF3 could not activate several types of promoters with NF-кB binding sites, including those from WSSV genes (wsv069, wsv056, and wsv403), Drosophila AMPs or shrimp AMPs. Accordingly, the mRNA levels of shrimp AMPs did not significantly change when TRAF3 was knocked down during WSSV infection. Instead, we found that LvTRAF3 signaled through the IRF-Vago antiviral cascade. LvTRAF3 functioned upstream of LvIRF to regulate the expression of LvVago4 and LvVago5 during WSSV infection in vivo. Taken together, these data provide experimental evidence of the participation of LvTRAF3 in the host defense to WSSV through the activation of the IRF-Vago pathway but not the NF-кB pathway.